2022
DOI: 10.3389/fpls.2021.768584
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Number and Ribosome Gene Expression Altered in a Genome-Editing Mutant of REDUCED POLLEN NUMBER1 Gene

Abstract: The number of pollen grains varies within and between species. However, little is known about the molecular basis of this quantitative trait, in contrast with the many studies available on cell differentiation in the stamen. Recently, the first gene responsible for pollen number variation, REDUCED POLLEN NUMBER1 (RDP1), was isolated by genome-wide association studies of Arabidopsis thaliana and exhibited the signature of natural selection. This gene encodes a homolog of yeast Mrt4 (mRNA turnover4), which is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Pollen grain number in angiosperms is a key reproductive trait that has been studied extensively for decades. Despite its agricultural and evolutionary importance, the genetic basis of the pollen grain number has remained elusive, primarily due to its quantitative nature [ 72 ]. The information generated from gene annotations allows us to focus our efforts on 19 genes related to male sterility over the 67 genes annotated in the genomic region identified by the QTL analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen grain number in angiosperms is a key reproductive trait that has been studied extensively for decades. Despite its agricultural and evolutionary importance, the genetic basis of the pollen grain number has remained elusive, primarily due to its quantitative nature [ 72 ]. The information generated from gene annotations allows us to focus our efforts on 19 genes related to male sterility over the 67 genes annotated in the genomic region identified by the QTL analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the other growth-related genes or other mutations of AT3G13882 might have reduced the aphid abundance. Because transgenic approaches may not be effective to identify mutation sites affecting quantitative traits, further experimental tests, such as quantitative complementation [16,40], will be needed to identify natural causal variants that alter aphid abundance through delayed growth.…”
Section: Discussionmentioning
confidence: 99%
“…While ribosomal genes have long been considered housekeeping genes of the protein synthesis machinery, mutants of ribosome-related genes exhibit a wide variety of growth and reproductive phenotypes. For example, previous studies reported the reduction of leaf cell number [38], reduced root length [39], and the reduction of pollen number [16,40] regarding ribosomal gene mutations. In this context, our findings from the ribosomal gene AT3G13882 add insights into biotic interactions besides growth deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MRT4 plays an important role in cell tolerance in yeast [ 19 ]. The loss of At RDP1 (the homolog of MRT4) could decrease the amount of pollen in Arabidopsis thaliana and inhibit its development, possibly due to ribosome specialization [ 20 ]. It was shown that the subcellular localization of human MRT4 is regulated by the C-terminal region under stress [ 21 ].…”
Section: Introductionmentioning
confidence: 99%